ANALISIS PENGARUH BOPO, EAR, LAR DAN FIRM SIZE TERHADAP KINERJA KEUANGAN (Studi kasus pada bank umum konvensional yang terdaftar di Bursa Efek Indonesia periode 2008-2011) - Kurnia, Indra; Mawardi, Wisnu (Diponegoro Journal of Management, 2012)
This study aims to determine the effect of Operating Expenses to Operating Income (BOPO), Equity to Total Assets Ratio (EAR), Loan to Assets Ratio (LAR) and firm size on Return on Assets (ROA). This study used four independent variables, namely BOPO, EAR, LAR, and firm size, with one dependent variable is Return on Assets (ROA). Sampling technique used was purposive sampling criteria (1) banking company listed in Indonesia Stock Exchange and has the most complete financial statements and have been published in the Bank Indonesia during the observation period from 2008 to 2011, (2) conventional commercial banks have already listing before the end observation period. Data obtained by the publication of financial statements listed on the website of Bank Indonesia. Obtained the sample of 12 companies. Analysis technique used is multiple regression, the assumptions of classical test and test hypotheses using t-statistics, testing the coefficient of determination and F-statistics to test the effect of the joint - the same as the level of significance of 5%. It also tested the classical assumptions that included tests of normality, multicollinearity test, test of heteroscedasticity, and autocorrelation test. Based on the results of data analysis, showed that: BOPO variables, firm size, loan to Assets Ratio (LAR) has a positive and significant impact on Return on Assets (ROA). The variable Equity to Total Assets Ratio (EAR) has a negative effect but not significant and have the smallest impact on Return on Assets (ROA).